(untitled) (Iraqi Journal of Market Research and Consumer Protection, 2025)
The chemical composition of both the leaves and stems of the Portulaca oleraceae L was evaluated the protein content of the leaves was slightly higher than the stems in Portulaca oleraceael, content of leaves were 4.025%, was slightly higher than stems 3.952%, as for the percentage of total fat, it turned out that the leaves contain a higher fat percentage than the stems and was as follows: The proportion of total fat content in leaves 0.4998% was higher than stems 0.3 68%. the moisture content in the leaves and stem was 71.6% and 82.7 % In addition, the fibers, ash and carbohydrates in leaves and stems as estimated at 3.0183% and 2.6613%, 6.1 %, and 4.4 %, 14.7 and 5.9 respectively. The total phenolic compounds and total flavonoids evaluated, it was noted that the alcoholic extract of the leaves had highest content of total phenols and total flavonoids, followed by the alcoholic extract of the stems and then the aqueous extract of the leaves, and the lowest content of total phenols were 98.448, 88.909, 70.689, 25.286 ppm respectively, and the flavonoids were 22.26, 18.22, 16.99, 13.45 mg / 100 respectively. The Antioxidant activity was evaluated by DPPH method, where the antioxidant activity was measured and several concentrations were taken (50, 100, 150, 200 and 250) mg/ml and the removal rate of free radicals was calculated, the best removal rate was foe the leaves alcoholic extract at 150 mg/ mL with 100% of removal rate, followed by the stems alcoholic extract with 98.32% removal rate as well as leaves equeous exract in removal rate was 96.65% Finally, the stems aqueous extract had removal rate 84.10% in the same concentration. 150 mg/ml, which is the best concentration that gave a 100% removal rate.